2014
DOI: 10.1016/j.nbd.2014.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin improves peripheral nerve myelination while it fails to benefit neuromuscular performance in neuropathic mice

Abstract: Charcot-Marie-Tooth disease type 1A (CMT1A) is a hereditary peripheral neuropathy characterized by progressive demyelination and distal muscle weakness. Abnormal expression of peripheral myelin protein 22 (PMP22) has been linked to CMT1A and is modeled by Trembler J (TrJ) mice, which carry the same leucine to proline substitution in PMP22 as affected pedigrees. Pharmacologic modulation of autophagy by rapamycin in neuron-Schwann cell explant cultures from neuropathic mice reduced PMP22 aggregate formation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…My findings support the results of previous studies, which have shown that nerve injury upregulates LC3 [98,99]. Rapamycin has been shown to protect against neurodegeneration by activating autophagy [100], and improves myelination in PNS [101]. Proteomic study of the injured nerves of diabetic rats 4 weeks after surgery identified 798 proteins, and among these 193 proteins were differentially expressed.…”
Section: Resultssupporting
confidence: 89%
“…My findings support the results of previous studies, which have shown that nerve injury upregulates LC3 [98,99]. Rapamycin has been shown to protect against neurodegeneration by activating autophagy [100], and improves myelination in PNS [101]. Proteomic study of the injured nerves of diabetic rats 4 weeks after surgery identified 798 proteins, and among these 193 proteins were differentially expressed.…”
Section: Resultssupporting
confidence: 89%
“…In light of the novel data indicating a prodifferentiating effect of mTORC1 inhibition in SCs, rapamycin treatment may also be a therapeutic option in neuropathies in which SC differentiation is defective, often a clinically severe condition. Intriguingly, administration of rapamycin has already been shown to decrease p75 expression levels, a marker for immature and promyelinating SCs, and to increase myelin proteins and myelinated fibers in a mouse model of hereditary neuropathy (Nicks et al, 2014). Such a therapeutic approach would be potentially favored by the intrinsic biological plasticity of SCs, which—unlike OLs—are capable of dedifferentiation/demyelination and redifferentiation/remyelination (Kim, Mindos, & Parkinson, 2013).…”
Section: Myelination and Mtormentioning
confidence: 99%
“…In subsequent studies RM was administered to neuropathic mice either by dietary supplementation or i.p. injections (Nicks et al, 2014). In both paradigms, peripheral nerves of RM-treated neuropathic mice showed significant improvements in myelin, however without benefit to neuromuscular function (Nicks et al, 2014).…”
Section: Small Molecule Therapiesmentioning
confidence: 99%
“…injections (Nicks et al, 2014). In both paradigms, peripheral nerves of RM-treated neuropathic mice showed significant improvements in myelin, however without benefit to neuromuscular function (Nicks et al, 2014). One explanation for this functional outcome might involve the distinct response of nerve and muscle tissue to the inhibition of mTOR (Quy et al, 2013).…”
Section: Small Molecule Therapiesmentioning
confidence: 99%